Rethinking Teaching Methods for Meaningful Learning in Contemporary Education - Ulan Susilawati, Ahmad Sulhan, Akhmad Syahri (Journal of Educational Studies, 2025)
Contemporary education is experiencing significant transformation due to rapid technological development, globalization, and evolving learner needs, requiring teaching methods that promote meaningful learning rather than passive knowledge transmission. This study aims to rethink teaching methods by examining how contemporary pedagogical practices support meaningful learning in classroom contexts. A qualitative-dominant mixed-method approach was employed involving 15 participants consisting of five teachers and ten secondary-level students in East Lombok Regency. Data were collected through classroom observations, semi-structured interviews, document analysis, and student questionnaires, and analyzed using an interactive analysis model complemented by descriptive statistics. The findings indicate a clear shift from teacher-centered instruction toward student-centered learning, where teachers act as facilitators of knowledge construction. Four major themes emerged from the analysis. First, student-centered learning promoted active participation, with 78% of students agreeing that classroom activities enabled active engagement. Second, collaborative learning enhanced interaction and motivation, supported by 82% student agreement. Third, contextual learning connected lessons to real-world experiences, with 85% of students perceiving learning as meaningful and relevant. Fourth, autonomy-supportive practices fostered learner independence, as 76% of students reported increased responsibility for their own learning. Triangulation across observations, interviews, documents, and questionnaires confirmed that redesigned teaching methods contributed to deeper engagement, contextual understanding, and learner autonomy. The study concludes that meaningful learning emerges when teaching integrates active participation, collaboration, contextual relevance, and reflective independence, aligning with contemporary educational demands and 21st-century learning competencies.